Social inclusion, poverty eradication and the 2030 agenda for sustainable development - Esuna Dugarova (United Nations Research Institute for Social Development (UNRISD), 2015)
The concept of social inclusion, also referred to as social integration or social cohesion, represents a vision for "a society for all" in which every individual, each with rights and responsibilities, has an active role to play (Report of the World Summit for Social Development, 1995). While various definitions have been developed to describe social inclusion, they all have been grounded in the promotion of a normative vision of society, in which individuals, groups or institutions are interconnected within a wider social system, and their relationships are maintained and enhanced in a harmonious way. This paper refers to social inclusion as a goal, process and outcome. As a universal goal, social inclusion aims to achieve an inclusive society that entails respect for human rights, cultural diversity and democratic governance, and upholds principles of equality and equity. As a process, it enables citizens participation in decision-making activities that affect their lives, allowing all groups to take part in this process, especially marginalized groups. As an outcome, it ensures the reduction of inequalities, elimination of any forms of exclusion and discrimination, and achievement of social justice and cohesion. Since the concept of social inclusion gained prominence following the World Summit for Social Development held in Copenhagen in 1995, there has been a tendency to (i) treat it as an expanded version of "economic" inclusion; (ii) identify exclusion with the marginalization of certain individuals or groups based on their race, ethnicity or gender; and (iii) focus on individual well-being in analysing and measuring social inclusion. Over time, however, it has become evident that, like other social ills such as poverty and inequality, exclusion has multiple causes and takes diverse forms related to age, disability and location, among others. It is therefore important to adopt a more comprehensive approach to inclusion. Furthermore, there has been a renewed interest in social inclusion, with a number of policies and programmes having been implemented around the world, which highlighted the need for the simultaneous promotion of productivity, poverty reduction and greater inclusiveness. The recognized limits in the Millennium Development Goals have generated calls for more transformative and universal policies that are better integrated across social, economic and environmental domains within a more coherent development framework. The Second UN Decade for the Eradication of Poverty (2008-2017) has further reiterated the need to address social exclusion and called for more inclusive approaches to overcome poverty in its multiple dimensions. In some countries, social programmes are now evolving towards a social inclusion framework, which incorporates (i) access to basic services, particularly health and education, requiring the active participation of beneficiaries in relevant programmes; and (ii) access to economic opportunities with the focus on inclusion in the labour market, with an overarching goal to reduce poverty and vulnerability, particularly among the most disadvantaged groups. This paper argues that there are three key interrelated areas that are critical for poverty eradication and inclusive development, which include (i) universal social protection; (ii) meaningful participation; and (iii) social and solidarity economy. It discusses some of the main issues related to these areas and provides examples of best practices at the national level that have been implemented during the UN Decades for the Eradication of Poverty. The paper concludes that it is unlikely that development will be sustainable unless it is inclusive. The 2030 Agenda for Sustainable Development thus needs to be an inclusive plan of action, pursuing the goal of leaving no one behind in the way that meets the needs of present generations without compromising the ability of future generations to participate in the processes that impact their lives. Social policies that promote practices based on universal rights-based entitlements, equal and meaningful participation, as well as norms of solidarity and reciprocity, while paying due respect to diversity and the environment, are more likely to enable social inclusion. It is therefore necessary to move away from the use of social inclusion schemes as remedial action towards making them an intrinsic part of broader and coherent development strategies. Government interventions in the form of enhancement of productive capacities, improved access to quality social services, adequate social protection and decent work are crucial to achieving socially inclusive, broad-based and sustainable development. Under this approach, social policy should be concerned not only with the welfare and rights of an individual but also with supporting social relations, institutions and structures through which the welfare of individuals in their households, communities and nations could be sustained and improved, while recognizing the importance of societal levels of analysis and not simply economic or individual indicators.
Keywords: 330